THEORETICAL STUDY OF CHLORINATION REACTION OF NITROBENZENE FROM DFT CALCULATIONS - MBOUOMBOUO, Ibrahim NDASSA; Bebga, Gouet; Signé, Martin; Volatron, François; Silvi, Bernard (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The geometric parameters of stationary points on the potential surface energy of the chlorination reaction of nitrobenzene in the presence of Aluminium chloride as catalyst were investigated theoretically by hybrid DFT (Density Functional Theory) calculations in order to determine his general reaction mechanism in gas phase and in solution. The results obtained by DFT have been compared with CCSD(T) method which is the most powerful post-Hartree Fock method in terms of inclusion of dynamic correlation. Although the electrophilic substitution reaction is widely taught in most courses in organic chemistry, the mechanism has been very few studied theoretically. The results obtained in gas phase are consistent with the traditional description of these reactions: the orientation of this substitution in meta position depends on the stability of a reaction intermediate (Wheland said). Without taking in consideration the reactants and products, six stationary points are found on the potential surface energy of this reaction. The reaction has also been studied in the presence of solvent and we’ve noted that the influence of solvent decreases the electrostatic attraction on the Wheland complex, but the general reaction mechanism remains unchanged in solution.